El dia mas feliz de Alicia - Starr, Meg.; Hu, Ying-Hwa; Van Wright, Cornelius; Fiol, Maria A. (New York, N.Y. : Star Bright Books, 2002)
Alicia receives greetings from her Hispanic neighborhood as she walks to her birthday party.
Accelerated Reader AR
Keywords: Birthdays; Parties; Hispanic Americans; Spanish language materials; Juvenile literature; Juvenile fiction